General practitioners' perceptions of sharing workload in group practices: qualitative study - Branson, Ruben (BMJ Publishing Group Ltd., 2004)
Objective To explore general practitioners' beliefs and experiences of distribution of workload and teamwork between doctors in general practice. Design Qualitative semistructured interview study. Setting South London. Participants 18 general practitioners from 11 practices. Main outcome measures Perceptions and experiences of distribution of workload and teamwork between doctors. Results Equitable distribution of workload was a common concern among general practitioners in group practices. Several ways of addressing the problem were identified, including relying on trust, creating systems of working based on explicit rules such as points' systems, and improving communication. Improvement of communication was hampered by the taboo nature of the problem. Conclusion Resentment about perceived inequalities in workload places a further burden on general practices. The issue of working together warrants further support.